Manajemen Strategi NU TV9 Menghadapi Televisi Swasta Lokal di Surabaya - Mochammad Dawud; Abdul Choliq (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2020)
Television 9 (TV9) is a private broadcast station owned by the East Java Regional Board of Nahdlatul Ulama (PWNU). TV9 is faced with the NU-style management issues that are thick with pesantren (Islamic boarding school) characteristics, both in terms of human resources and the management system developed by the media company. However, the applied management has actually made TV9 able to reach the maximum audience. The researchers employed qualitative methods. Through such method, this research obtained the results, namely; First, it is owned and managed by Nahdlatul Ulama (NU), as a business entity, TV9 is pursuing profit. TV9 management is managed with the aim of obtaining a very large marketing content for urban Muslims, especially the nahdliyin (NU community). TV9 is able to design programs based on the characteristics and interests of the nahdliyin community so that it gets a positive reception and affects its increase in performance share and ratings. Second, as a religious television station, TV9 prefers